Does Debt Discourage Employment and Payment of Child Support? Evidence from a Natural Experiment - Cancian, Maria; Heinrich, Carolyn J.; Chung, Yiyoon (My University, 2009)
The authors find an inverse relationship between child support debt and a father's earnings and child support payments. Higher arrears are generally associated with lower payments and lower earnings for fathers, although the patterns vary with fathers’ age and work histories.